2008
DOI: 10.1111/j.1463-5224.2008.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for selected ophthalmic diagnostic tests of the capuchin monkey (Cebus apella)

Abstract: Results for selected ocular diagnostic tests investigated here for the capuchin monkey eye were as follows: IOP: 18.4 +/- 3.8 mmHg; STT: 14.9 +/- 5.1 mm/min; CCT: 0.46 +/- 0.03 mm. No statistically significant differences between ages or genders were found for any of the results. Streptococcus sp. and Corynebacterium sp. were isolated from healthy conjunctival and eyelid margins, suggesting they are normal constituents of the conjunctival flora of the capuchin monkey. The data obtained in this investigation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
4
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 38 publications
(50 reference statements)
10
32
4
2
Order By: Relevance
“…The present study, along with others (22-24), does not confirm the reports that IOP significantly changes with age (7,13,28). In our literature review, except for a study on humans (37) and a study on lions (24), none of recent studies (22,23,25,30,36) has reported a significant relationship between the sex variable and IOP. The present study confirms these findings, since no significant difference was found between the mean IOPs obtained with TonoVet ® and Tono-Pen Vet ® for male and female dogs of all ages.…”
Section: Methodscontrasting
confidence: 54%
“…The present study, along with others (22-24), does not confirm the reports that IOP significantly changes with age (7,13,28). In our literature review, except for a study on humans (37) and a study on lions (24), none of recent studies (22,23,25,30,36) has reported a significant relationship between the sex variable and IOP. The present study confirms these findings, since no significant difference was found between the mean IOPs obtained with TonoVet ® and Tono-Pen Vet ® for male and female dogs of all ages.…”
Section: Methodscontrasting
confidence: 54%
“…Reports of eye diseases and determination of parameters for normal ophthalmic tests in primates are scarce. There are reports of a retrobulbar tumor in a squirrel monkey ( Saimiri sciureus ) , an odontogenic intraorbital abscess in a capuchin monkey ( Cebus apella ) and determination of ophthalmic parameters in capuchin monkey ( Cebus apella ) , tear production in squirrel monkey ( Saimiri sciureus ) , black‐tufted marmosets , and rhesus monkey ( Macaca mulatta ) and intraocular pressure (IOP) in rhesus monkey ( Macaca mulatta ) . To perform a proper diagnosis in wild and exotic species is necessary to determine normal baseline parameters for ophthalmic tests.…”
Section: Introductionmentioning
confidence: 99%
“…The Schirmer's tear test (STT) evaluates production of the aqueous portion of the tear film and is traditionally used to diagnose keratoconjunctivitis sicca (KCS) . Tear production has been determined for several species including humans .…”
Section: Introductionmentioning
confidence: 99%
“…(Am J Vet Res 2015;76:149-154) lens luxation, glaucoma, and uveitis. 8 Applanation tonometry has been used to measure IOP in numerous clinically normal domestic and nondomestic animals, including dogs, 12-14 cats, 15,16 horses, 17 ponies, 18 dairy cattle, 19 sheep, 20 goats, 21,22 llamas, 23,24 alpacas, 23,24 rabbits, 25,26 rats, 27 ferrets, 28,29 chinchillas, 30 capybaras, 31 hedgehogs, 32 beavers, 33 Nubian ibex (Capra nubiana), 7 Grant zebras (Equus quagga boehmi), 7 oryxes, 34 Arabian oryxes (Oryx leucoryx), 7 Thomson gazelles (Eudorcas thomsonii), 35 elands, 36 fallow deer, 36 addax antelope, 34 impalas, 34 wildebeests, 34 rhinoceroses, 34 capuchin monkeys, 37 koalas, 38 and lions. 10,11 In recent years, measurement of IOP in animals has evolved tremendously with the development of portable handheld digital tonometers.…”
Section: Conclusion and Clinical Relevancementioning
confidence: 99%